2018
DOI: 10.1371/journal.ppat.1007253
|View full text |Cite|
|
Sign up to set email alerts
|

Shugoshin 1 is dislocated by KSHV-encoded LANA inducing aneuploidy

Abstract: Shugoshin-1 (Sgo1) protects the integrity of the centromeres, and H2A phosphorylation is critical for this process. The mitotic checkpoint kinase Bub1, phosphorylates H2A and ensures fidelity of chromosome segregation and chromosome number. Oncogenic KSHV induces genetic alterations through chromosomal instability (CIN), and its essential antigen LANA regulates Bub1. We show that LANA inhibits Bub1 phosphorylation of H2A and Cdc20, important for chromosome segregation and mitotic signaling. Inhibition of H2A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Mu et al found that SGOL1 expression levels are higher in prostate cancer tissues, and SGLO1 knockdown results in the inhibition of tumor cell proliferation, migration, and invasion [42]. In addition, SGOL1 has been found in other cancers (e.g., breast cancer and glioblastoma) [4345]. However, few studies have described the methylation state of SGOL1, and research on SGOL1 in CCA has been rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Mu et al found that SGOL1 expression levels are higher in prostate cancer tissues, and SGLO1 knockdown results in the inhibition of tumor cell proliferation, migration, and invasion [42]. In addition, SGOL1 has been found in other cancers (e.g., breast cancer and glioblastoma) [4345]. However, few studies have described the methylation state of SGOL1, and research on SGOL1 in CCA has been rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…LANA prevents Bub1-mediated phosphorylation of H2A at position T120 to influence Sgo1 localization, resulting in chromosomal instability [129] PEL cell lines (BC-3, JSC-1); in vitro infection (BJAB, HT1080); ectopic expression (BJAB, HEK293, HT1080)…”
Section: Viral Manipulation Of the Host Epigenomementioning
confidence: 99%
“…Lastly, a recent publication found that LANA interacts with Bub1, a component of the spindle checkpoint complex, to inhibit phosphorylation of histone 2A at residue T120 (H2AT120) [129]. LANA-dependent inhibition of H2AT120 phosphorylation resulted in dislocation of Sgo1, a protein which protects centromere integrity, and induction of aneuploidy.…”
Section: Rta (Lytic)mentioning
confidence: 99%
“…LANA, in addition to tethering of the KSHV genome regulates several cellular functions required for oncogenic transformation of infected cells. The major pathways modulated by KSHV-encoded LANA include cell cycle[19], apoptosis[20], Epithelial-Mesenchymal transition (EMT)[21, 22] and chromosome instability (CIN)[23]. Nevertheless, other KSHV-encoded latent genes also plays a major role in oncogenic transformation of infected cells.…”
Section: Introductionmentioning
confidence: 99%